(untitled) (Baghdad Science Journal, 2005)
The effect of some environmental factors in the loss rate for high weights virgins are full to the screwworm fly of the ancient world and included temperatures 15,20,25,30,35,40 study showed that the rate of loss in weight virgins advanced to full participants at a temperature of 15 C while notgets evolution